Plant species and products of the Traditional Chinese Phytotherapy in the Ciudade Autónoma de Buenos Aires, Argentina - Hurrell, Julio Alberto; Puentes, Jeremías P. (Ethnobiology and Conservation, 2017)
This paper is focused in medicinal plant species belonging to the Traditional Chinese Phytotherapy whose products are commercialized in the pluricultural context of the Ciudad Autónoma de Buenos Aires, Argentina. The Chinese immigrants segment, like other recent immigrants groups in the study area, introduce their own plant products into the local urban scenario. In this framework, not only enter the new products but also their knowledge and beliefs associated, that become part of the mosaic of the knowledge in the local pluricultural system. Thus, the urban botanical knowledge constitutes a complex that includes the knowledge linked to the origin traditions of the immigrants segments, and the nontraditional one: the knowledge taught and learned, and the transmitted by the media, including scientific knowledge. The plant products incorporated by Chinese immigrants to their own restricted commercial circuit (linked to their traditions) are invisible for the majority of the local inhabitants. However, some of these products enter the general commercial circuit (nontraditional) and become visible for all local population. This visualization of the plant products implies the transmission of its associated knowledge, a process enhanced by the mass media, mainly the Internet. The results are interpreted within this theoretical framework. Also, the main features of the Traditional Chinese Phytotherapy are summarized, due to its differences with our Western medicine. For the species considered the scientific names, botanical families, distribution, Chinese name and Latin denomination of the plant products, and the reference samples are indicated. For each species are included a list of its uses linked to traditions, and a revision work of the biological activity and effects evaluated (the validation context in terms of Western science). In the context of Urban Ethnobotany, the presence alone of invisible species is a significant issue because increases the local biocultural diversity (of useful plants, products, and its associated knowledge). Likewise, the species that become visible make evident the dynamics of changes in their visualization process, an adaptive phenomenon that allow the understanding of the local biocultural system complexity.